2021
DOI: 10.1155/2021/3579074
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization Treatment of Acute Ischemic Stroke Caused by Large-Artery Occlusion in the Elderly: A Comparative Analysis of “the Elderly” and “the Very Elderly”

Abstract: Objective. To assess whether the effectiveness and safety of recanalization therapy for acute ischemic stroke (AIS) caused by large-artery occlusion (LAO) differ between patients aged 60–79 years and patients aged ≥80 years. Methods. We analyzed prospective data of patients with LAO (≥60 years) who underwent recanalization therapy at the Department of Vascular Neurosurgery, New Era Stroke Care and Research Institute, PLA Rocket Force Characteristic Medical Center, from November 2013 to July 2017. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…We found that age, sex, stroke history, and arrival time have crucial influences on sNfL levels at admission in patients suffering from AIS, despite the degree of the brain lesion, which is generally consistent with previous studies and our experience [ 16 , 17 ]. The sNfL levels at admission were found to be positively correlated with the ASPECT scores and neurological deficits and negatively correlated with the prognosis of AIS patients.…”
Section: Discussionsupporting
confidence: 92%
“…We found that age, sex, stroke history, and arrival time have crucial influences on sNfL levels at admission in patients suffering from AIS, despite the degree of the brain lesion, which is generally consistent with previous studies and our experience [ 16 , 17 ]. The sNfL levels at admission were found to be positively correlated with the ASPECT scores and neurological deficits and negatively correlated with the prognosis of AIS patients.…”
Section: Discussionsupporting
confidence: 92%